2022
DOI: 10.2196/33985
|View full text |Cite
|
Sign up to set email alerts
|

Use and Perception of Digital Health Technologies by Surgical Patients in Germany in the Pre–COVID-19 Era: Survey Study

Abstract: Background This survey study investigates surgical patients’ use and perception of digital health technologies in Germany in the pre–COVID-19 era. Objective The objective of this study was to relate surgical patients’ characteristics to the use and perception of several digital health technologies. Methods In this single-center, cross-sectional survey study in the outpatient department of a university hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The study published in the Journal of Medical Internet Research confirmed that AI-based decision support tools helped improve the accuracy and efficiency of rural telemedicine consultations. (14) Another study published in the Journal of Medical Systems witnessed that AI-based screening tools improved the detection of diabetic retinopathy in rural areas. (15) However, within the next ten years, artificial intelligence (AI) has the potential to transform the way healthcare is delivered in rural areas by improving the accessibility, affordability, and quality of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…The study published in the Journal of Medical Internet Research confirmed that AI-based decision support tools helped improve the accuracy and efficiency of rural telemedicine consultations. (14) Another study published in the Journal of Medical Systems witnessed that AI-based screening tools improved the detection of diabetic retinopathy in rural areas. (15) However, within the next ten years, artificial intelligence (AI) has the potential to transform the way healthcare is delivered in rural areas by improving the accessibility, affordability, and quality of healthcare services.…”
Section: Introductionmentioning
confidence: 99%